ChemInform Abstract: An Atom‐Economic Route to Thiophenes and 2, 2′‐Bithiophenes by Intramolecular Transannulation of gem‐Dialkylthio Enynes. Issue 1 (7th January 2014) - Fang, Guichun; Li, Jichun; Wang, Yeming; Gou, Mingyu; Liu, Qun; Li, Xingqi; Bi, Xihe
Abstract This novel, simple, and highly efficient method allows the synthesis of different functionalized thiophenes and bithiophenes.